1990
DOI: 10.1007/bf00317557
|View full text |Cite
|
Sign up to set email alerts
|

Amino acids as determinants of host preference for the xylem feeding leafhopper, Homalodisca coagulata (Homoptera: Cicadellidae)

Abstract: Homalodisca coagulata is a highly polyphagous xylem feeder with distinct seasonal patterns in it's selection of host plants. These patterns were examined in relation to the amino acid content of the xylem for four common host species; Lagerstroemia indica, Baccharis halimifolia, Prunus persica, and Prunus salicina. Xylem fluid was collected from each host species at times when numbers of feeding leafhoppers were both low and high. In each case, concentrations of amino acids were greatest when numbers were high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
0
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(101 citation statements)
references
References 33 publications
6
89
0
3
Order By: Relevance
“…10% total nitrogen dry weight basis), which does not accord with earlier reports of low nitrogen levels resulting in poor larval survival (Myers & Post, 1981;Myers, 1985;Cates et al, 1987). Increased levels of nitrogen and other nutrients can lead to unbalanced amino acid profiles and high concentrations of organic acids in plant tissues (Williams & Cronin, 2004); consequently such diets can be detrimental and even toxic to insects (Reese, 1979;Brodbeck et al, 1990). Similar to our results, significantly fewer L. tityrus developing on plants growing in soils that had been treated with a nitrogenous fertilizer survived than on plants growing in un-fertilized soil (Fischer & Fiedler, 2000).…”
Section: Discussionmentioning
confidence: 73%
“…10% total nitrogen dry weight basis), which does not accord with earlier reports of low nitrogen levels resulting in poor larval survival (Myers & Post, 1981;Myers, 1985;Cates et al, 1987). Increased levels of nitrogen and other nutrients can lead to unbalanced amino acid profiles and high concentrations of organic acids in plant tissues (Williams & Cronin, 2004); consequently such diets can be detrimental and even toxic to insects (Reese, 1979;Brodbeck et al, 1990). Similar to our results, significantly fewer L. tityrus developing on plants growing in soils that had been treated with a nitrogenous fertilizer survived than on plants growing in un-fertilized soil (Fischer & Fiedler, 2000).…”
Section: Discussionmentioning
confidence: 73%
“…Genes underlying steps in the TCA cycle are retained, indicating capability for producing energy from carbon skeletons derived from sugar or from amino-acid catabolism. Xylem sap lacks sugar, and amino acids are the primary energy substrates available for use by xylem-feeding insects (Brodbeck et al, 1990). We hypothesize that the Sulcia-encoded glutamate dehydrogenase (GdhA) enables the generation of 2-oxoglutarate from glutamate and that this enters the SLs-PSPU as a substrate in the TCA cycle, providing a major source of ATP for the symbiotic system (Figure 3b).…”
Section: Genomic Evidence For Sls As An Evolutionary Recent Symbiont mentioning
confidence: 99%
“…We hypothesize that the Sulcia-encoded glutamate dehydrogenase (GdhA) enables the generation of 2-oxoglutarate from glutamate and that this enters the SLs-PSPU as a substrate in the TCA cycle, providing a major source of ATP for the symbiotic system (Figure 3b). This possibility would depend on availability of excess glutamate, while glutamine and asparagine comprise most amino acids in the xylem (Brodbeck et al, 1990). Glutamate could be provided by SLs PSPU, which retains intact gltBD, encoding glutamate synthase, the enzyme that catalyzes the production of glutamate from glutamine.…”
Section: Genomic Evidence For Sls As An Evolutionary Recent Symbiont mentioning
confidence: 99%
See 1 more Smart Citation
“…Brodbeck et al [23] reported that the total amino acid content in the xylem strongly correlated with the survival and development rates of xylem-feeding insects.…”
Section: Rice Seedling Chemical Compositionmentioning
confidence: 99%